Purifying Zen: Watsuji Tetsurō's Shamon Dōgen - Watsuji, Tetsurō; Bein, Steve (University of Hawaiʻi Press, 2011)
Dōgen's period of self-cultivation -- The first sermon -- The method and meaning of self-cultivation -- Shinran's compassion and Dōgen's compassion -- Concerning excellence -- Concerning social problems -- Criticism of art -- Dogen's "truth."